2017
DOI: 10.21776/ub.jrm.2017.008.01.7
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Penyerapan Energi Crash Box Pola Origami pada Pengujian Frontal Impact Posisi Angular Frontal

Abstract: In the car, the body structure is designed in such a way so as to transfer and absorb energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This is different from previous research, if in previous research crash box was modeled as square, then in this research, the crash box was modelled as rectangle adjusted to real condition of MPV car, as seen in figure 3 and 4, with 2 mm thick crash box. The origami pattern crash box modeling was performed by taking optimum geometry data from previous research [11,12], which were number 3, 5 and 7 with segments of 6, 3 and 5 respectively. The result of crash box modelling design was seen in Figure 3 and 4, both of them had the same dimensions of length, width and height.…”
Section: Methods 21 Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is different from previous research, if in previous research crash box was modeled as square, then in this research, the crash box was modelled as rectangle adjusted to real condition of MPV car, as seen in figure 3 and 4, with 2 mm thick crash box. The origami pattern crash box modeling was performed by taking optimum geometry data from previous research [11,12], which were number 3, 5 and 7 with segments of 6, 3 and 5 respectively. The result of crash box modelling design was seen in Figure 3 and 4, both of them had the same dimensions of length, width and height.…”
Section: Methods 21 Modellingmentioning
confidence: 99%
“…The next research is performed by Kusyairi, et al [11], they design the origami pattern crash box with the Taguchi method on high speed impact test, it is concluded that the origami pattern crash box is able to produce predictable collapse mode and the greatest absorption was geometry that has many and thick segments. Origami pattern crash box collision research on the direction of corner collision has also been performed by Bintarto et al [12] and Zhou et al [13], it is found that pre folded mode of origami pattern capable of producing predictable collapse mode. The development of origami pattern crash box on the addition of origami trapezoid geometry model is performed by Zhou et al [14] the development of origami pattern with reconfigurable polygonal cross-sections model is performed by Filipov et al [15] and the development of origami pattern on Axial crushing is performed by Song et al [16].…”
Section: Introductionmentioning
confidence: 93%
“…It shown that origami crash box is able to result predictable collapse mode and the biggest absorption is on those with many segments and geometry thickness. Research on origami crash box of corner collision was also conducted by Bintarto et al [4] and Zhou et al [5], it obtained that origami pre-folded was resulting predictable collapse mode.…”
Section: Introductionmentioning
confidence: 99%